Lipidomics Analysis of the Tears in the Patients Receiving LASIK, FS-LASIK, or SBK Surgery - Gao, Yan; Qi, Yuanyuan; Huang, Yue; Li, Xiaorong; Zhou, Lei; Zhao, Shaozhen (Frontiers in Medicine, 2021)
Purpose Tear film lipid layer (TFLL) plays a vital role in maintaining tear film stability and thus lipid composition of tears could greatly affect the physiological function and biophysical integrity of tear film. The objective of this study is to assess the tear lipid composition of patients receiving laser-assisted in situ keratomileusis (LASIK), femtosecond LASIK (FS-LASIK), or Sub-Bowman’s keratomileusis (SBK) surgery pre-operatively and post-operatively. Methods Tear samples were collected from patient's left eye who receiving LASIK (n=10), FS-LASIK (n=10), or SBK (n=10) surgery in week 0, week 1, week 4 and week 52. A rapid direct injection shotgun lipidomics workflow, MS/MSALL (less than 2 min/sample), was applied to examine tear lipidome. Results In week 52, SBK group demonstrated a similar lipidome profile as that of week 0 while FS-LASIK and LASIK group shifted away from week 0. Two lipids, GD3 27:4 and TAG 59:3, were found to be associated with lipidome changes pre-operatively and post-operatively. No statistical significance was found in overall lipid classes from FS-LASIK group. LASIK group showed significant alteration in phospholipid and sphingolipid over time while SBK groups demonstrated a significant difference in OAHFA and phospholipid. Conclusion LASIK showed the greatest impact on lipidome changes over time while SBK demonstrated minimal impact among three types of refractive surgeries after 1 year.